PENERAPAN STRATEGI PEMBELAJARAN PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LARUTAN ASAM DAN BASA DI KELASI XI IPA SMA NEGERI 2 PEKANBARU - Chintiya Dwi Puspita Arnez; Betty Holiwarni; Asmadi M Noer (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research on learning strategy of Process Oriented Guided Inquiry Learning (POGIL) has been done in SMAN 2 Pekanbaru. The purpose of the study is to improve learning achievement of learners on the subject of acidic and alkaline solutions in kelasi XI IPA SMAN 2 Pekanbaru. The research type is experimental research with randomized control group pretest-posttest. The sample of the study consisted of 2 classes, class XI IPA2 as the experimental class and class XI IPA5 as the control class selected randomly after homogeneity test. The experimental class applied POGIL learning strategy while control class was not applied POGIL learning strategy. Technical analysis of data used is t test. based on the test data analysis obtained t count> ttable is 1.92> 1.66, meaning the application of learning strategies POGIL can improve student learning achievement on the subject of acidic and alkaline solutions in class XI IPA SMA Negeri 2 Pekanbaru with the category of improvement achievement (N -Gain) which is 7.9 high.Keywords : Learning Achievement, POGIL Learning Strategy, Acid and Base Solution